Explosive Pleuritis - Jasdeep K Sharma; Thomas J Marrie (Canadian Journal of Infectious Diseases)
The objective of the present paper is to describe the clinical and computed tomography features of 'explosive pleuritis', an entity first named by Braman and Donat in 1986, and to propose a case definition. A case report of a previously healthy, 45-year-old man admitted to hospital with acute onset pleuritic chest pain is presented. The patient arrived at the emergency room at 15:00 in mild respiratory distress; the initial chest x-ray revealed a small right lower lobe effusion. The subsequent clinical course in hospital was dramatic. Within 18 h of admission, he developed severe respiratory distress with oxygen desaturation to 83% on room air and dullness of the right lung field. A repeat chest x-ray, taken the morning after admission, revealed complete opacification of the right hemithorax. A computed tomography scan of the thorax demonstrated a massive pleural effusion with compression of pulmonary tissue and mediastinal shift. Pleural fluid biochemical analysis revealed the following concentrations: glucose 3.5 mmol/L, lactate dehydrogenase 1550 U/L, protein 56.98 g/L, amylase 68 U/L and white blood cell count 600 cells/mL. The pleural fluid cultures demonstrated light growth of coagulase-negative staphylococcus and viridans streptococcus, and very light growth of Candida albicans. Cytology was negative for malignant cells. Thoracotomy was performed, which demonstrated a loculated parapneumonic effusion that required decortication. The patient responded favourably to the empirical administration of intravenous levofloxacin and ceftriaxone, and conservative surgical methods in the management of the empyema. This report also discusses the patient's rapidly progressing pleural effusion and offers a potential case definition for explosive pleuritis. Explosive pleuritis is a medical emergency defined by the rapid development of a pleural effusion involving more than 90% of the hemithorax over 24 h, which causes compression of pulmonary tissue and mediastinal shift to the contralateral side.